Biopolitics, space and hospital reconfiguration. (June 2019) - Fraser, Alec; Baeza, Juan; Boaz, Annette; Ferlie, Ewan
Abstract: Major service change in healthcare – whereby the distribution of services is reconfigured at a local or regional level - is often a contested, political and poorly understood set of processes. This paper contributes to the theoretical understanding of major service change by demonstrating the utility of interpreting health service reconfiguration as a biopolitical intervention. Such an approach orients the analytical focus towards an exploration of the spatial and the population – crucial factors in major service change. Drawing on a qualitative study from 2011–12 of major service change in the English NHS combining documentary analyses of historically relevant policy papers and contemporary policy documentation (n = 125) with semi-structured interviews (n = 20) we highlight how a particular 'geography of stroke' in London was created building upon multiple types of knowledge: medical, epidemiological, economic, demographic, managerial and organisational. These informed particular spatial practices of government providing legitimation for the significant political upheaval that accompanies NHS service reconfiguration by problematizing existing variation in outcomes and making these visible. We suggest that major service change may be analysed as a 'practice of security' – a way of redefining a case, conceiving of risks and dangers, and averting potential crises in the interests of the population. Highlights: Foucault's work on biopolitics is applied to analyse major service change. The reconfiguration of stroke services in London is explored. Empirical and theoretical implications are discussed.